Frequency of Hypomagnesemia in Patients with Diabetes Mellitus at Civil Hospital Karachi (Medical Forum Monthly, 2024)
Objective: To determine frequency of hypomagnesemia in diabetic patients presenting at Civil Hospital Karachi.Study Design: Cross-sectional studyPlace and Duration of Study: This study was conducted at a Diabetic Clinic in National Institute of Diabetes and Endocrinology (NIDE), Karachi from January to June 2016.Materials and Methods: All patients > 12 years of age of either sex, diagnosed cases of diabetes mellitus (either Type I or Type II) of > 5 years duration and have given consent for participation in the study were included. Patients with acute pancreatitis and have history of alcoholism (such conditions results in reallocation of the magnesium from extracellular to intracellular space), occurrences of diarrhea, regurgitating and nasogastric suction, ostomies and gastrointestinal fistulas (conditions which result gastrointestinal magnesium loss) and patients receiving diuretics, chemotherapeutic agents (cisplatin), antimicrobials (amphotericin B, aminoglycosides, pentamidine, capreomycin. vancomycin, and foscarnet), immunosuppressants (tacrulimus and cyclosporine), and proton-pump inhibitors,(as all these drugs results in renal loss of magnesium)were excluded.Results: The average age of selected patients with diabetes mellitus was 46.81±6.8 years. Of 350 patients, 203 (58%) were female and 147 (42%) were male; 176 (50.3%) patients had diabetes for >= 7years; 269 (76.9%) patients had type II diabetes and 275 (78.6%) had uncontrolled diabetes. The mean serum magnesium level was 1.48±0.36 mg/dl and the frequency of hypomagnesemia was 227 (64.9%) cases.Conclusion: It is concluded from this study that the frequency of hypomagnesemia was 64.9% among study population.